Animal Fat Wastes for Biodiesel Production - Feddern, Vivian; Junior, Anildo Cunha; Prá, Marina Celant De; Abreu, Paulo Giovanni de; Filho, Jonas Irineu dos Santos; Higarashi, Martha Mayumi; Sulenta, Mauro; Coldebella, Arlei (IntechOpen, 2011)
None